Pengaruh Terapi Akupresure CV17 terhadap Kecemasan Ibu Hamil Trimester III di PMB “S” - Rofiqo Larasati Philip; Anisya Selvia (Jurnal Ventilator, 2026)
Pregnancy in the third trimester affects significant physical and psychological changes in pregnant women, psychological changes such as emotional changes, depression, stress, and anxiety. These conditions cause discomfort during pregnancy. Anxiety management can be done with pharmacological and non-pharmacological therapeutic approaches. Pharmacological therapy in pregnant women can carry the risk of side effects for the fetus, such as low birth weight (LBW) and cesarean delivery. Therefore, non-pharmacological therapy is a safer option, one of which is acupressure therapy. Efforts to help reduce anxiety in pregnant women include acupressure therapy, namely the CV17 point located in the fourth intercostal space (2-3 fingers above the epigastrium). Pressure on the CV 17 point will activate sensory nerve cells and then send signals to the spinal cord, stimulating the release of serotonin and endorphins that play a role in reducing anxiety. This study aims to determine the effect of CV17 acupressure therapy on anxiety in third-trimester pregnant women at PMB 'S'. The study was conducted on 20 third-trimester pregnant women experiencing anxiety. The research design used a pre-experimental method with one group pretest-posttest. The results of the study showed that there was an effect of CV17 acupressure therapy on anxiety in third trimester pregnant women in PMB 'S'. It is hoped that acupressure therapy can be used as a non-pharmacological alternative in an effort to reduce anxiety in pregnant women, especially in third trimester pregnant women.